2222: An accessible game to promote environment protection awareness - Peixoto, Amanda Bueno C.; Silva, Gabriel M.; Sarmiento, Jean B. R.; Rosa, Ulisses D. S.; Mota, Virgínia F. (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2022)
Accessibility in games remain largely inaccessible to visually and hearing impaired people. In this work, we introduce 2222, an accessible maze game that promotes a real inclusion, through resources such as auditory orientation and equity in the game mechanics, reducing the disparity in the game-play experience between players. Furthermore, we also brought environmental awareness within our narrative to inspire players to transform our reality.